Treatment and respiratory support modes for neonates with respiratory distress syndrome. (3rd May 2020) - Dassios, Theodore; Ambulkar, Hemant; Greenough, Anne
ABSTRACT: Introduction: Respiratory distress syndrome (RDS) remains an important problem. Identifying effective treatments and respiratory support modes is essential. Areas covered: Current treatments and respiratory support modes and the evidence base for new therapies and respiratory modes have been examined. Methods: A literature search was undertaken using PubMed and Google Scholar. Expert opinion: It is now common to stabilise infants on non-invasive respiratory support in the delivery suite and give early selective surfactant to infants with RDS. Increasingly, less invasive surfactant administration is used. Systemically administered corticosteroids should not be given in the perinatal period; inhaled budesonide has been associated with an increased mortality. Inhaled nitric oxide can be helpful in preterm infants with pulmonary hypertension. Caffeine should be routinely administered. Further research regarding stems cells is required. Post extubation, nasal intermittent positive pressure ventilation (NIPPV) rather than nasal continuous positive airway pressure (nCPAP) provides better support and humidified high flow nasal cannula (HHFNC) has similar efficacy to continuous positive airway pressure (CPAP). Volume targeting should be used for infants requiring intubation. There is insufficient evidence to determine the role of neurally adjusted ventilatory assist or whether closed loop automatic oxygen control improves long term outcomes.